Business models for renewable energy in the built environment - International Energy Agency (Abingdon, Oxon : Routledge, 2013)
Business Models for Renewable Energy in the Built Environment provides insight to policy makers and market actors as to the ways that new and innovative business models (and/or policy measures) can stimulate the deployment of renewable energy technologies (RET) and energy efficiency (EE) measures in this field. This project was initiated and funded by the IEA Implementing Agreement for Renewable Energy Technology Deployment (IEA-RETD). It analyses ten business models in three categories, covering different types of energy service companies (ESCO{u3A6E}
Includes bibliographical references and index.
Keywords: Real estate development -- Environmental aspects; Residential real estate -- Environmental aspects; Sustainable buildings -- Economic aspects; Sustainable construction -- Economic aspects; Renewable energy sources -- Economic aspects